Development of Contextual Numeracy Literacy Tool based on 21st Century Skills in MI Al-Ishlah Kota Sorong Southwest Papua - ., Mulyono; Yaumi, Muhammad; Ibrahim, Misykat Malik; Achruh, Andi; Ituga, Almuhaimin Sarnav; Permana, Imam; ., Andrianto (Journal of Posthumanism, 2025)
The numeracy literacy skills of madrasah students are still relatively low, while the challenges of the 21st century demand mastery of critical thinking, problem solving, and logical thinking skills in the context of real life. This study aims to develop and analyze the effectiveness of numeracy literacy learning tools integrated with 21st century skills at MI Al-Ishlah Sorong City. The device development uses the Plomp model which consists of five phases: initial investigation, design, realization/construction, test-evaluation-revision, and implementation. The results of the needs analysis showed that the device was needed by teachers (85%) and students (86.7%). Expert validation showed that the device met the eligibility criteria, with a language validation score of 80.25%, media 91.4%, and content 88.6% and 86.4%. The practicality of the device was rated high based on the responses of learners (86.17%) and teachers (85.17%), and in accordance with the audio- visual learning style of learners. The effectiveness of the module was tested with a one-group pretest- posttest design. The results showed a significant increase in the mean score from 57.95 to 80.6, with an N-Gain of 0.69. This device is proven to be able to improve the understanding of numeracy concepts as well as critical and creative thinking skills of learners. This study concludes that the device developed is valid, practical, and effective, and is recommended to be applied in learning as an innovative effort in strengthening numeracy competence in the 21st century learning era.